Peningkatan Kemampuan Kader Posyandu Deteksi Dini Kanker Payudara SADARI Kelurahan Serangan Denpasar - Ni Nyoman Budiani; Gusti Ayu Marhaeni; Sri Rahayu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Breast cancer is a non-communicable disease characterized by rapid and uncontrolled cell growth that can spread to other parts of the body. Breast cancer ranks first among all cancers (34.3%), followed by cervical cancer (19.12%). This community service activity aimed to enhance the capacity of cadres to perform breast self-examination (BSE) as an effort for early detection of breast cancer. The method employed was coaching, targeting all 70 Posyandu cadres (10 cadres per Posyandu). The coaching media consisted of modules and leaflets and was implemented through the delivery of educational materials on cancer and early detection, as well as demonstrations of BSE procedures. The results showed that knowledge levels, attitude scores, and skills were higher after the coaching intervention. In conclusion, coaching effectively improves the ability of Posyandu cadres to conduct early detection of breast cancer through BSE.